Antibody-Dependent Enhancement Activity of a Plant-Made Vaccine against West Nile Virus - Haiyan Sun; Dhiraj Acharya; Amber M. Paul; Huafang Lai; Junyun He; Fengwei Bai; Qiang Chen (Vaccines, 2023)
West Nile virus (WNV) causes annual outbreaks globally and is the leading cause of mosquito-borne disease in Unite States. In the absence of licensed therapeutics, there is an urgent need to develop effective and safe human vaccines against WNV. One of the major safety concerns for WNV vaccine development is the risk of increasing infection by related flaviviruses in vaccinated subjects via antibody-dependent enhancement of infection (ADE). Herein, we report the development of a plant-based vaccine candidate that provides protective immunity against a lethal WNV challenge mice, while minimizes the risk of ADE for infection by Zika (ZIKV) and dengue (DENV) virus. Specifically, a plant-produced virus-like particle (VLP) that displays the WNV Envelope protein domain III (wDIII) elicited both high neutralizing antibody titers and antigen-specific cellular immune responses in mice. Passive transfer of serum from VLP-vaccinated mice protected recipient mice from a lethal challenge of WNV infection. Notably, VLP-induced antibodies did not enhance the infection of Fc gamma receptor-expressing K562 cells by ZIKV or DENV through ADE. Thus, a plant-made wDIII-displaying VLP presents a promising WNV vaccine candidate that induces protective immunity and minimizes the concern of inducing ADE-prone antibodies to predispose vaccinees to severe infection by DENV or ZIKV.